Acod1-mediated inhibition of aerobic glycolysis suppresses osteoclast differentiation and attenuates bone erosion in arthritis - Kachler, Katerina; Andreev, Darja; Thapa, Shreeya; Royzman, Dmytro; Gießl, Andreas; Karuppusamy, Shobika; Llerins Perez, Mireia; Liu, Mengdan; Hofmann, Jörg; Geßner, Arne; Meng, Xianyi; Rauber, Simon; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: Metabolic changes are crucially involved in osteoclast development and may contribute to bone degradation in rheumatoid arthritis (RA). The enzyme aconitate decarboxylase 1 (Acod1) is known to link the cellular function of monocyte-derived macrophages to their metabolic status. As osteoclasts derive from the monocyte lineage, we hypothesised a role for Acod1 and its metabolite itaconate in osteoclast differentiation and arthritis-associated bone loss. Methods: Itaconate levels were measured in human peripheral blood mononuclear cells (PBMCs) of patients with RA and healthy controls by mass spectrometry. Human and murine osteoclasts were treated with the itaconate derivative 4-octyl-itaconate (4-OI) in vitro. We examined the impact of Acod1-deficiency and 4-OI treatment on bone erosion in mice using K/BxN serum-induced arthritis and human TNF transgenic (hTNFtg) mice. SCENITH and extracellular flux analyses were used to evaluate the metabolic activity of osteoclasts and osteoclast progenitors. Acod1-dependent and itaconate-dependent changes in the osteoclast transcriptome were identified by RNA sequencing. CRISPR/Cas9 gene editing was used to investigate the role of hypoxia-inducible factor (Hif)-1α in Acod1-mediated regulation of osteoclast development. Results: Itaconate levels in PBMCs from patients with RA were inversely correlated with disease activity. Acod1-deficient mice exhibited increased osteoclast numbers and bone erosion in experimental arthritis while 4-OI treatment alleviated inflammatory bone loss in vivo and inhibited human and murine osteoclast differentiation in vitro. Mechanistically, Acod1 suppressed osteoclast differentiation by inhibiting succinate dehydrogenase-dependent production of reactive oxygen species and Hif1α-mediated induction of aerobic glycolysis. Conclusion: Acod1 and itaconate are crucial regulators of osteoclast differentiation and bone loss in inflammatory arthritis.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Bone Density; Inflammation; Osteoporosis

A new platform for autoimmune diseases. Inducing tolerance with liposomes encapsulating autoantigens - Almenara-Fuentes, Lidia; Rodriguez-Fernandez, Silvia; Rosell-Mases, Estela; Kachler, Katerina; You, Axel; Salvado, Miriam; Andreev, Darja; Steffen, Ulrike; Bang, Holger; Bozec, Aline; Schett, Georg; Le Panse, Rozen; et al. (Nanomedicine : nanotechnology, biology, and medicine, 2023)
Autoimmune diseases (AIDs) are caused by the loss of self-tolerance and destruction of tissues by the host's immune system. Several antigen-specific immunotherapies, focused on arresting the autoimmune attack, have been tested in clinical trials with discouraging results. Therefore, there is a need for innovative strategies to restore self-tolerance safely and definitively in AIDs. We previously demonstrated the therapeutic efficacy of phosphatidylserine (PS)-liposomes encapsulating autoantigens in experimental type 1 diabetes and multiple sclerosis. Here, we show that PS-liposomes can be adapted to other autoimmune diseases by simply replacing the encapsulated autoantigen. After administration, they are distributed to target organs, captured by phagocytes and interact with several immune cells, thus exerting a tolerogenic and immunoregulatory effect. Specific PS-liposomes demonstrate great preventive and therapeutic efficacy in rheumatoid arthritis and myasthenia gravis. Thus, this work highlights the therapeutic potential of a platform for several autoimmunity settings, which is specific, safe, and with long-term effects.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Autoimmune diseases; Immunotherapy; Myasthenia gravis; Nanomedicine; Preclinical mouse models; Rheumatoid arthritis

Eosinophils preserve bone homeostasis by inhibiting excessive osteoclast formation and activity via eosinophil peroxidase. - Andreev, Darja; Kachler, Katerina; Liu, Mengdan; Chen, Zhu; Krishnacoumar, Brenda; Ringer, Mark; Frey, Silke; Krönke, Gerhard; Vöhringer, David; Schett, Georg; Bozec, Aline (Nature Communications, 2024)
Eosinophils are involved in tissue homeostasis. Herein, we unveiled eosinophils as important regulators of bone homeostasis. Eosinophils are localized in proximity to bone-resorbing osteoclasts in the bone marrow. The absence of eosinophils in ΔdblGATA mice results in lower bone mass under steady-state conditions and amplified bone loss upon sex hormone deprivation and inflammatory arthritis. Conversely, increased numbers of eosinophils in IL-5 transgenic mice enhance bone mass under steady-state conditions and protect from hormone- and inflammation- mediated bone loss. Eosinophils strongly inhibit the differentiation and demineralization activity of osteoclasts and lead to profound changes in the transcriptional profile of osteoclasts. This osteoclast-suppressive effect of eosinophils is based on the release of eosinophil peroxidase causing impaired reactive oxygen species and mitogen-activated protein kinase induction in osteoclast precursors. In humans, the number and the activity of eosinophils correlates with bone mass in healthy participants and rheumatoid arthritis patients. Taken together, experimental and human data indicate a regulatory function of eosinophils on bone.
EVALuna2:554518

Epithelial HIF2 alpha expression induces intestinal barrier dysfunction and exacerbation of arthritis - Wen, Jinming; Lyu, Pang; Stolzer, Iris; Xu, Jin; Gießl, Andreas; Lin, Zhen; Andreev, Darja; Kachler, Katerina; Song, Rui; Meng, Xianyi; Cao, Shan; Guggino, Giuliana; et al. (Annals of the Rheumatic Diseases, 2022)
To investigate how the mucosal barrier in the intestine influences the development of arthritis, considering that metabolic changes in the intestinal epithelium influence its barrier function. Intestinal HIF2α expression peaked at onset of experimental arthritis and RA. Conditionally, deletion of HIF2α in gut epithelial cells inhibited arthritis and was associated with improved intestinal barrier function and less intestinal and lymphatic Th1 and Th17 activation. Mechanistically, HIF2α induced the transcription of the pore-forming claudin (CLDN)-15, which inhibits intestinal barrier integrity. Furthermore, treatment with HIF2α inhibitor decreased claudin-15 expression in epithelial cells and inhibited arthritis and littermate control mice. The gut intestinal HIF2α target genes were delineated by chromatin immunoprecipitation and luciferase experiments. Furthermore, pharmacological HIF2α inhibitor PT2977 was used for inhibition of arthritis. These findings show that the HIF2α-CLDN15 axis is critical for the breakdown of intestinal barrier function at onset of arthritis, highlighting the functional link between intestinal homeostasis and arthritis.
CRIS-Team WoS Importer:2022-07-01
Keywords: Arthritis; Arthritis; Experimental; Inflammation.

IL-9 Producing Tumor-Infiltrating Lymphocytes and Treg Subsets Drive Immune Escape of Tumor Cells in Non-Small Cell Lung Cancer - Heim, Lisanne; Yang, Zuqin; Tausche, Patrick; Hohenberger, Katja; Chiriac, Mircea-Teodor; Kölle, Julia; Geppert, Carol-Immanuel; Kachler, Katerina; Miksch, Sarah; Graser, Anna; Friedrich, Juliane; Kharwadkar, Rakshin; et al. (Frontiers in Immunology, 2022)
Although lung cancer is the leading cause of cancer deaths worldwide, the mechanisms how lung cancer cells evade the immune system remain incompletely understood. Here, we discovered IL-9-dependent signaling mechanisms that drive immune evasion in non-small cell lung cancer (NSCLC). We found increased IL-9 and IL-21 production by T cells in the tumoral region of the lung of patients with NSCLC, suggesting the presence of Th9 cells in the lung tumor microenvironment. Moreover, we noted IL-9 producing Tregs in NSCLC. IL-9 target cells in NSCLC consisted of IL-9R+ tumor cells and tumor-infiltrating lymphocytes. In two murine experimental models of NSCLC, and in vitro, IL-9 prevented cell death and controlled growth of lung adenocarcinoma cells. Targeted deletion of IL-9 resulted in successful lung tumor rejection in vivo associated with an induction of IL-21 and reduction of Treg cells. Finally, anti-IL-9 antibody immunotherapy resulted in suppression of tumor development even in established experimental NSCLC and was associated with reduced IL-10 production in the lung. In conclusion, our findings indicate that IL-9 drives immune escape of lung tumor cells via effects on tumor cell survival and tumor infiltrating T cells. Thus, strategies blocking IL-9 emerge as a new approach for clinical therapy of lung cancer.
CRIS-Team Scopus Importer:2022-05-20
Keywords: IL-9; immune escape; NSCLC; TIL; tumor immunotherapy

L-Arginine metabolism inhibits arthritis and inflammatory bone loss - Cao, Shan; Li, Yixuan; Song, Rui; Meng, Xianyi; Fuchs, Maximilian; Liang, Chunguang; Kachler, Katerina; Meng, Xinyu; Wen, Jinming; Schlötzer-Schrehardt, Ursula; Taudte, Verena; Geßner, Arne; et al. (Annals of the Rheumatic Diseases, 2023)
Objectives: To investigate the effect of the L-Arginine metabolism on arthritis and inflammation-mediated bone loss. Methods: L-Arginine was applied to three arthritis models (collagen-induced arthritis, serum-induced arthritis and human TNF transgenic mice). Inflammation was assessed clinically and histologically, while bone changes were quantified by μCT and histomorphometry. In vitro, effects of L-Arginine on osteoclast differentiation were analysed by RNA-seq and mass spectrometry (MS). Seahorse, Single Cell ENergetIc metabolism by profilIng Translation inHibition and transmission electron microscopy were used for detecting metabolic changes in osteoclasts. Moreover, arginine-Associated metabolites were measured in the serum of rheumatoid arthritis (RA) and pre-RA patients. Results: L-Arginine inhibited arthritis and bone loss in all three models and directly blocked TNFα-induced murine and human osteoclastogenesis. RNA-seq and MS analyses indicated that L-Arginine switched glycolysis to oxidative phosphorylation in inflammatory osteoclasts leading to increased ATP production, purine metabolism and elevated inosine and hypoxanthine levels. Adenosine deaminase inhibitors blocking inosine and hypoxanthine production abolished the inhibition of L-Arginine on osteoclastogenesis in vitro and in vivo. Altered arginine levels were also found in RA and pre-RA patients. Conclusion: Our study demonstrated that L-Arginine ameliorates arthritis and bone erosion through metabolic reprogramming and perturbation of purine metabolism in osteoclasts.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Arthritis; Inflammation; Osteoporosis

L-ARGININE REPROGRAMS OSTEOCLAST PURINE METABOLISM AMELIORATING BONE LOSS IN RHEUMATOID ARTHRITIS - Cao, Shan; Song, Rui; Meng, Xianyi; Kachler, Katerina; Fuchs, Maximilian; Meng, X.; Li, Y.; Taudte, Verena; Kunz, Meik; Schlötzer-Schrehardt, Ursula; Schleicher, Ulrike; Chen, X.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Rheumatoid arthritis and osteoimmunology: The adverse impact of a deregulated immune system on bone metabolism - Andreev, Darja; Kachler, Katerina; Bozec, Aline; Schett, Georg (Bone, 2022)
The term osteoimmunology describes an interdisciplinary research field that links the investigation of osteology (bone cells) with immunology. The crosstalk between innate and adaptive immune cells and cells involved in bone remodeling, mainly bone-resorbing osteoclasts and bone-forming osteoblasts, becomes particularly obvious in the inflammatory autoimmune disease rheumatoid arthritis (RA). Besides striking inflammation of the joints, RA causes bone loss, leading to joint damage and disabilities as well as generalized osteoporosis. Mechanistically, RA-associated immune cells (macrophages, T cells, B cells etc.) produce high levels of pro-inflammatory cytokines, receptor activator of nuclear factor κB ligand (RANKL) and autoantibodies that promote bone degradation and at the same time counteract new bone formation. Today, antirheumatic therapy effectively ceases joint inflammation and arrests bone erosion. However, the repair of established bone lesions still presents a challenging task and requires improved treatment options. In this review, we outline the knowledge gained over the past years about the immunopathogenesis of RA and the impact of a dysregulated immune system on bone metabolism.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Bone erosion; Osteoblasts; Osteoclasts; Osteoimmunology; Rheumatoid arthritis

Systemic PPAR gamma Antagonism Reduces Metastatic Tumor Progression in Adipocyte-Rich Bone in Excess Weight Male Rodents - Gaculenko, Anastasia; Gregoric, Gasper; Popp, Vanessa; Seyler, Lisa; Ringer, Mark; Kachler, Katerina; Wu, Zhengquan; Kisel, Wadim; Hofbauer, Christine; Hofbauer, Lorenz C.; Uder, Michael; Schett, Georg; et al. (Journal of Bone and Mineral Research, 2021)
Primary tumors are widely associated with an excess in body fat. The role of adipose tissue on tumor cell homing to bone is yet poorly defined. In this study, we aimed to assess whether bone colonization by tumor cells is favored by an adipocyte-rich bone marrow. We delineated the accompanying alterations of the bone microenvironment and established a treatment approach that interferes with high fat diet (HFD)-induced bone metastasis formation. We were able to show that adipocytes affect skeletal tumor growth in a metastatic model of breast cancer in male rats and melanoma in male mice as well as in human breast cancer bone biopsies. Indeed, HFD-induced bone marrow adiposity was accompanied by accelerated tumor progression and increased osteolytic lesions. In human bone metastases, bone marrow adiposity correlated with tumor cell proliferation. By antagonization of the adipocyte differentiation and storage pathway linked to the peroxisome proliferator-activated receptor gamma (PPAR gamma) with bisphenol-A-diglycidylether (BADGE), we were able to decelerate tumor progression and subsequent osteolytic damage in the bones of two distinct metastatic animal models exposed to HFD. Overall these data show that adipose tissue is a critical factor in bone metastases and cancer-induced bone loss. 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team WoS Importer:2021-09-03